Teacher Support on Students' Attitude toward Research Writing - Digamon, Jayson; De La Pena, Jerome (JPAIR Multidisciplinary Research, 2022)
Discussions on research writing have always been associated with the teachers' role in influencing students' attitudes to pursue it. This study determined the teachers' role in students' attitudes toward research writing. This study was focused on the 124 Grade 12 students of Gingoog City Comprehensive National High School, Gingoog City, who took up Practical Research 2 subject using the mixed explanatory methodology research design. With descriptive statistics and linear regression analysis, the influence of teacher support on students' attitudes toward research writing was examined. The results revealed that students in their research writing experienced strong teacher support. Likewise, it was shown that teacher support directly impacts students' attitudes toward research. The study concluded that while other factors may affect students' attitudes toward research writing, the teacher factor was among the most significant. This further implies the need for teachers to provide students with holistic support, specifically instructional, to handle the subject effectively and sustain the students' interest in writing their papers.
Keywords: research writing; teacher support; mixed explanatory; Philippines